2007
DOI: 10.1523/jneurosci.4051-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fast Synaptic Vesicle Reuse Slows the Rate of Synaptic Depression in the CA1 Region of Hippocampus

Abstract: During short-term synaptic depression, neurotransmission rapidly decreases in response to repetitive action potential firing. Here, by blocking the vacuolar ATPase, alkalinizing the extracellular pH, or exposing hippocampal slices to pH buffers, we impaired neurotransmitter refilling, and electrophysiologically tested the role of vesicle reuse in synaptic depression. Under all conditions, synapses onto hippocampal CA1 pyramidal cells showed faster depression with increasing stimulation frequencies. At 20 Hz, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 59 publications
5
56
2
Order By: Relevance
“…In hippocampal or neocortical neurons, rapidly recycled SVs in the RRP are capable of rapid reuse (45) and slow the rate of synaptic depression (46). Our study shows that synaptic transmission in cultured SCG neurons also decreases rapidly in response to repetitive action potential firing (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…In hippocampal or neocortical neurons, rapidly recycled SVs in the RRP are capable of rapid reuse (45) and slow the rate of synaptic depression (46). Our study shows that synaptic transmission in cultured SCG neurons also decreases rapidly in response to repetitive action potential firing (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…To investigate the properties of single synaptic vesicle exocytosis and endocytosis, we expressed the pHluorin-tagged version of the vesicular glutamate transporter (vGlut-pHluorin) in dissociated hippocampal cultures (Voglmaier et al, 2006) using a lentiviral expression system (Ertunc et al, 2007). Earlier work has shown that vGlut-pHluorin expression results in low levels of surface fluorescence, enabling reliable detection of single vesicle fusion events (Balaji and Ryan, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found increased short term depression that occurred at lower stimulus frequencies in DBA mice. Impairment of fast vesicle recycling may result in a frequency-dependent increase in short term depression in hippocampal CA1 synapses, which may emerge in early phases (300 ms at 20 Hz) of stimulation (36). Taken together, these observations suggest differences in replenishment of the readily releasable pool in DBA mice.…”
Section: Volume 290 • Number 25 • June 19 2015mentioning
confidence: 86%